Analisis Putusan Pengadilan Tinggi Makassar Nomor 105/PDT/2022/PT.MKS Terhadap Eksekusi Hak Tanggungan Kreditur - Sadono, Awang Hardian (Faculty of Law Universitas Islam Indonesia, 2024)
One of the government's policies in the banking world is the implementation of credit provision which carries a risk of failure or congestion in credit repayment. To anticipate these risks, guarantees are needed. In banking practice, the issue of collateral is important because collateral is protection for creditors such as banks and is a form of the debtor's seriousness in fulfilling his obligations in repaying credit. The use of land as collateral for credit is based on the consideration that land is the safest and has relatively high economic value and can be tied to mortgage rights and clear and certain execution so that the funds that have been spent can immediately be returned to the creditor (bank), and these funds can be used in turnover. economic wheels. However, in practice, all the conveniences and advantages of the Mortgage Rights execution process based on Article 6 of the Mortgage Rights Law cannot always be utilized by banks as an alternative for resolving problem loans guaranteed by Mortgage Rights. There are many problematic factors that cause the mortgage rights execution process to not run as it should. The factors of this problem include various things, including the incompatibility of the legal substance of the Mortgage Rights Law which regulates the mortgage rights execution process itself, the actions and paradigms of law enforcement officials, as well as the legal culture that exists in society, including the paradigm of the debtor as the executed party. Mortgage right. This research aims to examine and analyze the process of executing Mortgage Rights in court and the considerations of the Panel of Judges in deciding the case. From the research results, it can be stated that the basis used by the judge in deciding the case is in accordance with the applicable regulations, however, in resolving bad credit itself, it would be better if you used the 3R alternative (rescheduling, reconditioning, restructuring) before carrying out the mortgage rights execution process. which then ends up in court or through judicial channels.